Linguistic basis of consecutive interpreting in scientific and technical texts. - Smagulova., A. S. (Journal of Oriental Studies, 2016)
The article deals with linguistic basis consistent translation of scientific and technical texts. Problems arising from the translation are more related to the transfer of special vocabulary, and only professionals working in a certain area can pick up a certain equivalent of a particular term. But the basic contradictionsin the scientific and technical texts is a contradiction between the desire for maximum completeness and accuracy of the transformation of language units, at the same time, the translator should strive for brevity. The use of different means and methods of lexical and syntactic compression inherent in scientific andtechnical literature, allows to achieve coherence of the text and to resolve the issue between accuracy and economically.